China’s Alipay and WeChat Pay : Reaching Rural Users - Aveni, Tyler; Roest, Joep (World Bank, Washington, DC, 2018)
Chinese information technology conglomerates Alibaba and Tencent own or operate dozens of competing online businesses, and yet, their affiliate mobile wallets stand out for how they have fundamentally influenced everyday living in China’s cities. Alibaba through its dominance in e-commerce and Tencent through its mobile social media and messaging platforms (WeChat and QQ) connect mass-market audiences with their respective wallet products of Alipay and WeChat Pay. Although these services are the product of unique market conditions, they offer many learning opportunities. Perhaps most extraordinary has been the companies’ ability to build trust with users. Tencent and Ant Financial, Alibaba’s financial affiliate, are redefining the relationship users have with finance. Finance is becoming simpler, and it is also remarkably more social in nature. This holds great promise for advancing rural financial inclusion in China. However, challenges in serving last-mile clients remain.